2015
DOI: 10.1016/j.medengphy.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided three-dimensional needle steering in biological tissue with curved surfaces

Abstract: In this paper, we present a system capable of automatically steering a bevel-tipped flexible needle under ultrasound guidance toward a physical target while avoiding a physical obstacle embedded in gelatin phantoms and biological tissue with curved surfaces. An ultrasound pre-operative scan is performed for three-dimensional (3D) target localization and shape reconstruction. A controller based on implicit force control is developed to align the transducer with curved surfaces to assure the maximum contact area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…Recent studies have presented systems that use a steerable needle with prior identification of parameters that minimize target motion [6], or that track motion and correct the insertion of a straight needle [7]. Other studies attempt to predict tissue motion using finite-element (FE) modelling to improve pre-operative planning [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have presented systems that use a steerable needle with prior identification of parameters that minimize target motion [6], or that track motion and correct the insertion of a straight needle [7]. Other studies attempt to predict tissue motion using finite-element (FE) modelling to improve pre-operative planning [8].…”
Section: Introductionmentioning
confidence: 99%
“…For the accurate needle steering, it is necessary to track the position of the needle tip and the tumor in real time. Abayazid et al and Wang et al proposed path planning for a flexible, bevel-tipped needle by obtaining the needle tip position and the target position in real time with ultrasonic and video camera image guidance (Abayazid et al, 2015;Wang et al, 2014). However, with respect to the anatomical site of this study, tracking the needle tip position in the lower abdomen using ultrasonic imaging is difficult, because of signal decay from bowel gas.…”
Section: Introductionmentioning
confidence: 87%
“…Preliminary studies have demonstrated that steering is challenging in biological tissue, because the tissue is heterogeneous and the needle deflection varies in different parts of the tissue [12]. In this work, we are moving our research towards more clinically-relevant conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies use softtissue simulants made from homogeneous gelatin phantoms, in which the needle can be easily located from the ultrasound images. Vrooijink et al attached an ultrasound transducer to a Cartesian robot [12], [19]. They combined 2D ultrasound images with transducer position feedback to track the needle in 3D, both in gelatin phantoms and in biological tissue.…”
Section: Introductionmentioning
confidence: 99%